Field Testing of the Use of Intake24—An Online 24-Hour Dietary Recall System - Maisie K. Rowland (Nutrients, 2018)
Dietary assessment is important for monitoring and evaluating population intakes. Online tools can reduce the level of participant burden and the time taken to complete records, compared with other methods. The study aimed to field test an online dietary recall tool (Intake24) to test the suitability for collecting dietary information in Scottish national surveys and to develop the system based on feedback and emerging issues. Previous Scottish Health Survey participants, aged 11+ years, were invited to complete Intake24 and provide feedback about it. Of those who agreed to take part, 60% completed at least one recall. Intake24 was found to be user-friendly, enjoyable to use, and easy to follow and understand. Users agreed they would like to use Intake24 often, (44% compared with 15% who disagreed) and >75% felt the system accurately captured their dietary intakes. The main challenge reported was finding foods within the database. Of those completing fewer recalls than requested, the majority reported that they believed they had completed the required number or reported not receiving emails requesting they complete a further recall. Intake24 was found to be a user-friendly tool allowing dietary assessment without interviewer presence. Feedback indicated the method for recall reminders needs to be refined and tailored.